1986
DOI: 10.1111/j.1469-8137.1986.tb00623.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF PHOTON IRRADIANCE ON THE GROWTH OF SHOOTS AND ROOTS, ON THE RATE OF INITIATION OF MYCORRHIZAL INFECTION AND ON THE GROWTH OF INFECTION UNITS IN TRIFOLIUM SUBTERRANEUM L.

Abstract: SUMMARYThe effects of photon irradiance on the growth of young plants (up to three weeks old) of Trifolium subterraneum L. and on the development of mycorrhizal root systems were studied with plants grown in a soil/sand mixture inoculated with Glomus mosseae (Nicol. & Gerd.) Gerdemann & Trappe. Total plant growth was lower when phototi irradiance was 100 //mol m~'^ s~', compared with 450 /nnol m"^ s"'. Fresh weight of shoots was unaffected, but the fresh weight/dry weight ratio was increased at the lower irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 41 publications
(51 reference statements)
7
55
0
Order By: Relevance
“…If this were not the case, we would expect a higher proportion of root length to be colonized by the fungus at elevated CO # , since more C is being sent below ground by the host plant. Indeed, mycorrhizal colonization rates are generally thought to be dependent on the carbohydrate status of the host plant ; for example, Tester et al (1986) have shown that, in Trifolium subterraneum, the mycorrhizal colonization rate was lower at lower irradiance (i.e. at lower C availability).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…If this were not the case, we would expect a higher proportion of root length to be colonized by the fungus at elevated CO # , since more C is being sent below ground by the host plant. Indeed, mycorrhizal colonization rates are generally thought to be dependent on the carbohydrate status of the host plant ; for example, Tester et al (1986) have shown that, in Trifolium subterraneum, the mycorrhizal colonization rate was lower at lower irradiance (i.e. at lower C availability).…”
Section: mentioning
confidence: 99%
“…Obtaining time-course data, which allows the study of biomass partitioning between plant parts (i.e. allocation patterns), is therefore particularly important when studying mycorrhizas in the context of CO # concentrations, since the amount of fixed C going to the roots can play a role in mycorrhizal colonization (Tester et al, 1986). If data for single harvests are used, the only available measure of allocation pattern (between two plant parts) will be a ratio or fraction ; however, if there is a difference in total plant size between the two treatments (as it often is at different CO # levels), then such comparisons are meaningless.…”
Section: mentioning
confidence: 99%
“…Our results do not seem to support this interpretation. If light was the only factor limiting the formation of mycorrhizas, a reduction in irradiance of 50%, which is enough to have a negative effect on mycorrhizal structures in T. subterraneum (Tester et al, 1985(Tester et al, , 1986, should result in a lower percentage infection. However, in the second experiment low light intensity did not modify infection.…”
Section: mentioning
confidence: 99%
“…plants at non-saturating irradiances of either 400 or 180 µmol m −# s −" (Hesketh & Moss (1963) cited in Tester et al (1985Tester et al ( , 1986), provided by incandescent and fluorescent lamps. The light intensity was reduced by placing a frame with a plastic mesh over the corresponding subplots.…”
Section: Effects Of Mycorrhizas Density and Shadingmentioning
confidence: 99%
See 1 more Smart Citation